Job Crafting on Job Performance: The Mediating Role of Organizational Citizenship Behavior at Perum Perhutani KPH Nganjuk - Muhammad Rizal Aminul Khakim; Budiono Budiono (International Journal of Social, Economic, and Business, 2025)
This research aims to analyze the influence of Job Crafting on Job Performance through Organizational Citizenship Behavior at Perum Perhutani KPH Nganjuk. This research uses a quantitative approach. The population of this study were employees of Perum Perhutani KPH Nganjuk and the sample size collected was 45 respondents. The data in this study were analyzed using SEM-PLS which was processed with SmartPLS 3.9.2 software. The analysis results obtained from this research show that job crafting has a positive and significant effect on job performance. Job crafting has a positive and significant effect on organizational citizenship behavior. Organizational citizenship behavior has a positive and significant effect on job performance. Job crafting has a positive and significant effect on job performance through organizational citizenship behavior.